Electrophysiological responses to appetitive and aversive outcomes: A comparison of college drinkers and non-drinkers. (1st January 2020) - Soder, Heather E.; Suchting, Robert; Potts, Geoffrey F.
Highlights: Non-drinkers displayed a larger feedback-related negativity to aversive outcomes compared to rewards. Drinkers had a blunted feedback-related negativity to aversive outcomes compared to non-drinkers. College drinkers are less sensitive to aversive outcomes, which could contribute to alcohol use. Abstract: The current study compared electrophysiological responses (the feedback-related negativity [FRN]) to appetitive and aversive outcomes between a group of college drinkers and non-drinkers. 50 undergraduate students completed a passive, slot machine-like task while their electroencephalographic data was recorded to extract the FRN to unexpected appetitive and aversive outcomes. In the appetitive condition, participants could expectedly or unexpectedly win 1 or not win 1 and in the aversive condition participants could expectedly or unexpectedly be exposed to a loud noise burst or silence. The FRN was recorded in response to a cue indicating the outcome. Participants also reported on the number of drinks they consumed in a typical week to establish drinking status (drinker/non-drinker). Results showed that non-drinkers had a larger FRN in the aversive task compared to the appetitive task while drinkers had similar FRNs between the tasks. Drinkers had a significantly smaller aversive outcome related FRN compared to non-drinkers. Neural sensitivity to aversive outcomes might be a marker of decreased punishment sensitivity in college drinkers compared to non-drinkers, contributing to unhealthy drinking behavior.